Entrepreneurship and innovation within the creative economy: the case of creative entrepreneurs in Rio de Janeiro - Lyonnet, Charlotte (2016)
Within the creative economy, private sectors are mainly represented by entrepreneurship and micro companies as long as artistic activities are usually the fruit of the core expertise of a professional named the creative expert. In this field, creativity has a twofold approach. On one hand, it is the main asset a creative expert has, artistically speaking. On the other hand, it is the essence of an entrepreneur to generate innovation. They both meet in creative clusters where the nice blend between cultural, creative and social capitals makes creative thinking combine with entrepreneurial spirit to produce innovation. In the case of Rio de Janeiro, the main characteristics of the creative economy are well embodied by the Brazilian culture. From this observation, this study aims to investigate how Brazilian creative experts and entrepreneurs meet and make creative clusters spring to support them to come up with innovation. In Rio de Janeiro, entrepreneurship within creative clusters is analyzed at the heart of its cultural and emotional complexity in order to understand the Brazilian approach of conducting a creative business. For this purpose, the ecosystem of the creative economy of Rio de Janeiro is first described to understand, in a second time, how creative clusters meet competitiveness to reach innovation. Finally, a quantitative and qualitative research assesses Brazilian creative entrepreneurs’ business model canvas to reveal their creative approach with innovation.